Chronic pelvic pain in the community--symptoms, investigations, and diagnoses. - Zondervan, K; Yudkin, P; Vessey, M; Jenkinson, C; Dawes, MG; Barlow, D; Kennedy, S (2001)
OBJECTIVES: This study was undertaken to investigate the overlap between chronic pelvic pain, dysmenorrhea, dyspareunia, irritable bowel syndrome, and genitourinary symptoms in the community and also to examine associated investigations and diagnoses. STUDY DESIGN: A postal questionnaire was used to survey 3916 women aged 18 through 49 randomly selected from the Oxfordshire Health Authority Register. The number of responders was 2304 (74% of 3106 questionnaire recipients). Chronic pelvic pain was described as recurrent or constant pelvic pain of > or =6 months' duration unrelated to periods, intercourse, or pregnancy. Case patients (n = 483) were subgrouped as follows: (1) chronic pelvic pain only, (2) chronic pelvic pain and irritable bowel syndrome, (3) chronic pelvic pain and genitourinary symptoms, and (4) chronic pelvic pain, genitourinary symptoms, and irritable bowel syndrome. RESULTS: Half the women with chronic pelvic pain also had either genitourinary symptoms or irritable bowel syndrome, or both. Prevalences of dysmenorrhea and dyspareunia were higher among women with chronic pelvic pain (81% and 41%, respectively) than among women without chronic pelvic pain (58% and 14%, respectively); rates did not differ among the chronic pelvic pain subgroups. Irritable bowel syndrome and stress were the most common diagnoses received by patients with chronic pelvic pain, but 50% had never received a diagnosis. CONCLUSIONS: There is substantial overlap between chronic pelvic pain and other abdominal symptoms in the community. Despite a high prevalence of chronic pelvic pain, many women have never had the condition diagnosed.